Penggunaan Pengembangan Virtual Reality Scratch sebagai Media Pembelajaran - Imas Dewi Orvala Nathania Insani; Revina Aurigha Firdaus; Handika Dio Pradana; Aditya Ramadhan Wahyu Santoso; Dodik Arwin Dermawan (Jurnal Informatika dan Teknologi Komputer (J-ICOM), 2023)
Visual-based programming is a method of making a program where the programmer connects objects by drawing, pointing and clicking on diagrams or icons and interacting with flowcharts. Visual-based programming itself uses visualization where there is the use of visual representations such as graphics, images or animations to describe a program, data, structure, or behavior of a complex dynamic system. In Scratch, there is a Windows-based programming language from Microsoft. Virtual Reality is the appearance of three-dimensional images made by computers so that they look real. with the rocks of some specific tools. With this Virtual Reality, users both children, students,